Safety and Efficacy of Retropubic or Transobturator Midurethral Slings in a Randomized Cohort of Turkish Women - TARCAN, TUFAN; TANIDIR, YILÖREN (KARGER, 2014)
Objective: The aim of this study was to evaluate the safety and efficacy of retropubic (RP) or transobturator (TO) midurethral slings (MUS) in a prospective randomized cohort of Turkish women. Patients and Methods: A total of 54 women with urodynamic stress urinary incontinence (SUI) were randomized to undergo either RP or TO MUS between August 2006 and February 2013 in a tertiary referral center by a single surgeon. All patients had history, physical examination, urodynamic evaluation and quality of life assessments. The validated Turkish versions of the SEAPI, ICIQ-SF and OAB-V8 questionnaires were used. The Advantage (R) RP and the Obtryx (R) TO MUS Systems were used for all RP and TO procedures. Results: Twenty-seven patients were randomized to each group. The median follow-up was 48.5 +/- 21.8 months. The median hospital stay was 24.0 +/- 4.8 h and median operative time was 35.0 +/- 19.9 min. The overall objective and subjective cure rates were 92.6 and 79.6%, respectively. The quality of life of all patients significantly increased after the operation compared to their preoperative status. Patients with a poorer subjective cure rate were those with mixed urinary incontinence, whose preoperative SEAPI and OAB-V8 scores were significantly higher. Conclusion: MUS surgery is highly effective and could safely be performed in a cohort of Turkish women with SUI in subspecialty centers by experienced surgeons. There is no significant difference between RP or TO applications in terms of safety and efficacy. Further studies with long-term follow-up data are required. (C) 2014 S. Karger AG, Basel
Keywords: Urinary incontinence; Midurethral sling; Vaginal mesh; Vaginal tape; STRESS URINARY-INCONTINENCE; FREE VAGINAL TAPE; COMPLICATIONS; MULTICENTER; MANAGEMENT; OUTCOMES; SURGERY; RISK; TVT